Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40